A Comparative Study on Water Quality Assessment of Shatt Al-Arab Estuary and Al-Ashar Canal, Basrah, Iraq - Kahami, Adian A.; Abdullah , Asia F.; Al-Shawi, Imad J. (Iraqi Journal of Aquaculture, 2023)
Monitoring water quality is absolutely essential for formulating policies that affect public and environmental health. The study samples were collected during the period from autumn 2021 to summer 2022, The study show the environmental deterioration of Al-Ashar canal compared with Shatt Al-Arab estuary. including some physical parameters: air and water temperature, which had the highest values in station 2 during July and reached 38.9 and 29 C°, respectively while salinity concentrations recorded a high at station 1. achieved (8.8) g/L. Turbidity and total suspended matter concentrations increased at station 3, achieving 106 NTU and 100 mg/L, respectively. Also the chemical and biological parameters in Al-Ashar Canal were very poor compared to the Shatt Al-Arab, including: pH, whose values were in the basal direction, and the highest values were recorded in station 3, achieving 8.89 Also, there was an increase in the values of the biological oxygen demand and chemical oxygen demand, achieving 2400 and 590 mg/L at stations 2 and 3 respectively. While a decrease was recorded in the dissolved oxygen values in station 3, which amounted to 0.13 mg /L, nutrients ( , and ) increased at station 3,2,2. achieving 1.79, 17.982 and 15.51 µg/L, respectively. Also, the values of chlorophyll A increased at station 2 and reached 215.72 µg/L. The aimed of the study is determined the water quality of Al-Ashar canal and compared with Shatt Al-Arab.